Sur la biométrie des mandibules et des dents humaines d’Ishango (LSA, République démocratique du Congo) - Rosine Orban; Patrick Semal; François Twiesselmann (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This work resumes and actualises the biometric study of Twiesselmannn (1990) on the comparison between the measurements performed on the Ishango fossils and those reported from other fossils and from two modern reference populations. The studied material is composed of a piece of mandible with M2 (Ishango A), of an isolated M1, and of two almost complete mandibles (Ishango a et D). The reference material comprises measurements of australopithecines, of Homo erectus, of Neandertals, and of fossil and recent Homo sapiens sapiens (medieval inhabitants from Belgium and contemporaneous inhabitants from Congo). Taking into account the reduction of teeth and maxillaries since the australopithecines until Homo sapiens sapiens, bivariate analyses have led to the following observations: the mandibles D and a tend to be located among the higher values of the modern variation; some of their measurements (a.o. those of the ascending ramus) are close to those from the fossils of the Upper Paleolithic of Europe, of Fish Hoek, and of Gamble Cave; the Ishango a mandible is more robust than the D mandible; its molars are larger, in relative terms, than the other teeth of the toothrow; the M2 from Ishango A and a are located within the variability of the Plio-Pleistocene fossils from Africa and of the Homo erectus; the large dimensions of the M1 dental germ locate it among the Australopithecines. While the dimensions of the D mandible seem consistent with the age of the deposits, the dimensions of Ishango A and a, and particularly of the germ of M1, are very large for the age of the layer where they have been found.